Anti- Japanese-Encephalitis-Viral Effects of Kaempferol and Daidzin and Their RNA-Binding Characteristics - Zhang, Ting; Wu, Zhiqiang; Du, Jiang; Hu, Yongfeng; Liu, Liguo; Yang, Fan; Jin, Qi (PLOS ONE, 2012)
Background New therapeutic tools and molecular targets are needed for treatment of Japanese encephalitis virus (JEV) infections. JEV requires an α-1 translational frameshift to synthesize the NS1' protein required for viral neuroinvasiveness. Several flavonoids have been shown to possess antiviral activity in vitro against a wide spectrum of viruses. To date, the antiviral activities of flavonol kaempferol (Kae) and isoflavonoid daidzin (Dai) against JEV have not been described. Methodology/Principal Findings The 50% cytotoxic concentration (CC50) and 50% effective concentration (EC50) against JEV were investigated in BHK21 cells by MTS reduction. Activity against viral genomic RNA and proteins was measured by real-time RT-PCR and western blotting. The frameshift site RNA-binding characterization was also determined by electrospray ionization mass spectrometry, isothermal titration calorimetry and autodocking analysis. EC50 values of Kae and Dai were 12.6 and 25.9 µM against JEV in cells pretreated before infection, whereas in cells infected before treatment, EC50 was 21.5 and 40.4 µM, respectively. Kae exhibited more potent activity against JEV and RNA binding in cells following internalization through direct inhibition of viral replication and protein expression, indicating that its antiviral activity was principally due to direct virucidal effects. The JEV frameshift site RNA (fsRNA) was selected as a target for assaying Kae and Dai. ITC of fsRNA revealed an apparent Kb value for Kae that was nine fold stronger than that for Dai. This binding was confirmed and localized to the RNA using ESI-MS and autodock analysis. Kae could form non-covalent complexes with fsRNA more easily than Dai could. Conclusions/Significance Kae demonstrates more potent antiviral activity against JEV than does Dai. The mode of action of Kae as an anti-JEV agent seems to be related to its ability to inactivate virus by binding with JEV fsRNA.